Ratio Legis of Combining Illegal Acts with Default in Small Claim Court Cases - Hadi, Abd; Suhartono, Suhartono (al-'adalah, 2023)
Civil procedural law in Indonesia has not yet specifically regulate the accumulation of lawsuits between Unlawful Acts (PMH) and default, which resulted in prolonged discourse in the realm of jurisprudence. Some legal experts are of the opinion that combining cases of unlawful acts with cases of breach of contract in one case/lawsuit is not permitted, seanwhile others think that such an accumulation is possible. The debates finally ended with the publication of the Supreme Court Regulation (PERMA) on Small Claims Court which provided legal certainty regarding the permissibility of this accumulation. This research is normative law with a substantive analysis approach. The aim is to find out the legal philosophical basis behind the formation of PERMA. The results of the research show that the possibility to cumulate between Unlawful Acts (PMH) and default in the PERMA aims to simplify the process of proceedings through simple, fast and low-cost principles. In this way, foreign investors'confidence in resolving cases in Indonesia can be increased.